816. Early Surgical Site Infections in High Risk Orthopedic Surgery Patients Following Change in Perioperative Antibiotic Selection. (4th December 2021) - Lee, Benjamin; Pasikhova, Yanina; Morrison, Austin R; Baluch, Aliyah; Binitie, Odion
Abstract: Background: Endoprosthestic or allograft reconstruction has become common following resection of malignant musculoskeletal tumors. Reported SSI rates after resection and reconstruction have been reported as high as 10 – 39% due to concurrent radiation and/or chemotherapy, compared to 0.6% - 2.0% in other orthopedic procedures. Though the optimal duration and perioperative antibiotic prophylaxis is well defined in other orthopedic procedures, there is little evidence to guide management in patients undergoing reconstruction with large endoprosthesis. At Moffitt Cancer Center (MCC), cefepime and vancomycin (FEP/VAN) were historically used for perioperative antibiotic prophylaxis; however, due to national logistical issues, these antibiotics were modified on June 6th, 2015 to cefazolin and vancomycin (CFZ/VAN). Methods: We report a pre-post quasi-experimental interrupted time-series non-inferiority study conducted at MCC with 150 high-risk orthopedic surgery patients with a primary objective of demonstrating non-inferiority of CFZ/VAN to FEP/VAN with reducing early SSI rates for patients after tumor resection followed by reconstruction. Statistical analysis was performed utilizing a multivariate logistic regression analysis of the interventions and primary outcome. Data were processed and analyzed within the R version 4.0.2 software. Results: Both groups included 75 patients with most common indications for surgery being sarcoma of any type (53%) and metastatic bone disease (27%), with the most common location of reconstruction at the distal femur (25%) and acetabulum (24%). Rates of early SSIs were low and numerically similar with 3 (4%) in the FEP/VAN group and 4 (5.4%) in the CFZ/VAN group. There was one instance of hardware removal due to infection within the FEP/VAN group. Baseline Characteristics Baseline characteristics for total study population, FEP/VAN, and CFZ/VAN Results including SSI rate, pathogens, infection Surgical site infection rates, culture site, group and interventions Conclusion: Overall, the rates of early SSI rates at MCC between both groups are numerically lower compared to previous studies. Between groups, the rates are similar and supports the use of CFZ/VAN in this patient population. The low rate of early SSIs in this study may be attributed to several factors such as extended oral antibiotic prophylaxis at discharge. Further analysis is ongoing to determine the statistical significance of any differences between confounding variables. Disclosures: All Authors : No reported disclosures